2023
DOI: 10.1007/s11250-023-03461-2
|View full text |Cite
|
Sign up to set email alerts
|

Fast growing broiler production from genetically different pure lines in Turkey. 2. Broiler traits: growth, feed intake, feed efficiency, livability, body defects and some heterotic effects

Abstract: The aim of the this study was to reveal the trends in body weight (BW), feed intake (FI), feed conversion ratio (FCR), livability, and body defects (foot pad dermatitis (FPD), hock burn (HB), and breast burn (BB)) in offspring of ANADOLU-T pure lines (PLs), their 12 four-way hybrids and ROSS-308 hybrid, and the observed heterosis values for some performance and body defect traits. A total of 2736 (1368 broilers each) broiler chickens from ANADOLU-T pure lines, their hybrids, and commercial ROSS-308 hybrid were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…This is because selection for growth rate after hatching is likely to have altered embryonic metabolism and heat production by affecting the developmental pattern of the embryo (óDea et al, 2004;Janke, 2004). A recent study showed that ROSS-308 chicks were superior to ANADOLU-T pure lines in terms of growth characteristics (Erensoy and Sarıca, 2023). This may partly explain the elevated body temperature associated with the relatively higher metabolic rate of ROSS-308 hybrids.…”
Section: Discussionmentioning
confidence: 99%
“…This is because selection for growth rate after hatching is likely to have altered embryonic metabolism and heat production by affecting the developmental pattern of the embryo (óDea et al, 2004;Janke, 2004). A recent study showed that ROSS-308 chicks were superior to ANADOLU-T pure lines in terms of growth characteristics (Erensoy and Sarıca, 2023). This may partly explain the elevated body temperature associated with the relatively higher metabolic rate of ROSS-308 hybrids.…”
Section: Discussionmentioning
confidence: 99%
“…The two are more distantly related, with more significant variation between traits and higher heterozygosity in the F2 generation. Thus the two populations are designed for forward and backward F2 crosses, which is conducive to genetic localization studies [ 70 ]. China has abundant livestock and poultry breed resources, and it will be important to use these breeds to establish reference lines to supplement the deficiencies in genomic studies.…”
Section: Discussionmentioning
confidence: 99%
“…Anadolu-T is a registered genotype for broiler production and is within the scope of the selection and breeding program in Türkiye. The pure lines of Anadolu-T and their crosses had lower body weights and impaired feed conversion ratios but a higher livability compared to commercial strains [28]. These chickens could be an alternative for niche markets and small local producers.…”
Section: Introductionmentioning
confidence: 95%